TRANSFORMATION OF THE WESTERN EDUCATION SYSTEM THROUGH ISLAMIC CONTRIBUTIONS: A HISTORICAL ANALYSIS - Abidin, Mustika; Hasyim Haddade; Muzakkir (al-Iltizam: Jurnal Pendidikan Agama Islam, 2024)
Islam is a religion that has moral values, especially rahmatan lil'alamin. As a universal religion, Islamic teachings are intended for everyone, regardless of place and time. This convinces the public that Islam and its teachings are the fundamental key in building social life. Historically, Islam has played an important role/contribution to global progress, including in the West. The Islamic world experienced a high level of civilizational hegemony. So there is indeed a contribution of Islam to the West. When the West was still dominated by Church doctrine which tended to reject scientific research and scientists were considered infidels, Christians and allowed Christians to be tortured and punished, the West experienced the Dark Ages. At that time, the Islamic world was busy with scientific research and development, resulting in the formation of a valuable civilization. This is what motivates Western scientists to study Islam in depth, especially science, and apply it to the West.